Pelatihan Pengenalan First Aid dan Bantuan Hidup Dasar untuk Para Kader di Desa Karangmulya, Kecamatan Bojongmangu - Rini Nurdini; Ummu Habibah; Lusi Noviyanti (Abdimas Universal, 2024)
First Aid in Accidents was a temporary relief and treatment effort for accident victims before receiving more complete assistance from health workers. This cannot be done if the community as the front guard does not have the understanding and skills in initial treatment. First aid was important for accident victims to avoid death or disability. Knowledge of Basic Life Support (BLS) was very necessary to handle these cases. This activity aims to increased knowledge and skills in providing Basic Life Support (BLS) for Health Cadres in Karangmulya village. The method used is training for cadres. The results of the t-test showed that the average pre-test knowledge of the training participants was 4.91 with a median of 4.5 for the pre-test, a standard deviation of 1.130 and an average post-test knowledge score of 6.67 with a standard deviation of 0.89 and a median of 7.00. It can be concluded that there was an increase in knowledge after training with an average difference of 2 scores. This data also shows that cadres are an asset as ordinary people are quick to receive information and learning for emergencies. It is hoped that this activity will be carried out periodically.